Risk of Hepatocellular Carcinoma Remains High in Patients with HBV-Related Decompensated Cirrhosis and Long-Term Antiviral Therapy - Dong-Mei Zhu; Jing Xie; Chun-Yan Ye; Mei-Yun Qian; Yuan Xue (Canadian Journal of Gastroenterology and Hepatology)
Background. This study aimed to evaluate the risk factors of HCC development in patients with hepatitis B virus (HBV)-related DC and who underwent long-term antiviral therapy. Methods. Data from 308 patients with HBV-related DC and long-term antiviral therapy were collected and retrospectively reviewed. Cox regression analysis was used to analyze independent risk factors of HCC development. Results. Data from 129 patients with definite records were analyzed. The median follow-up time was 5 years (range, 1 to 8 years). At the end of the follow-up, 41 (31.8%) patients developed HCC, and the time from DC diagnosis to HCC incidence who received antiviral therapy was 4.4 years (range, 1–7 years). The incidence of HCC was higher in males (30/78, 38.5%) than in females (11/51, 21.6%) (P = 0.04). Patients who developed HCC were significantly older than those who did not develop HCC (P < 0.01). The incidence of HCC in patients receiving nucleoside analogues, nucleotide analogues, and combination therapy was 34.7%, 38.1%, and 33.3%, respectively, and the difference showed no significant differences (P = 0.95). Multivariate Cox regression analysis demonstrated that male gender and age ≥50 years are independent risk factors of HCC development (OR = 2.987 and 2.408; 95% CI (1.301–6.858) and (1.126–5.149); P = 0.01 and 0.02, respectively). Conclusion. The risk of HCC remains to be high in patients with HBV-related DC, especially in males aged ≥50 years.